The Influence of Western Society's Construction of a Healthy Daily Life on the Conceptualisation of Occupation - Kantartzis, Sarah; Molineux, Matthew (Taylor & Francis Australasia, 2010)
This article proposes that the current conceptualisation of occupation within the dominant Anglophone literature reflects central elements of Western society's construction of a ‘healthy’ daily life, the ‘ideal’ and expected way to live. Contemporary theories of social action are used to describe the structuring influence of social institutions on daily activity. Four of the commonly identified characteristics of occupation, that it is active, purposeful, temporal and meaningful, are discussed in relation to Western institutions and related aspects of daily life. It is not intended to provide a comprehensive account of the socio-historical construction of the concept of occupation, but rather to illustrate the coherence of characteristics of occupation with those of Western daily life. The implications of this for understandings of occupation amongst groups and communities with alternative constructions of daily life are discussed. Some examples are offered, particularly from Greece, as a Christian Orthodox, non-industrialised, largely collectivistic society.